The practice of dining together in the origins of greek civic communities - Plácido, Domingo (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The symposium, from the beginning of hierarchized societies, set it self up as an instrument of social cohesion and control on the side of dominants. Centres where they hold were embryonic of sacred places which became, in the origins of archaism, temples that operated as centre for civic activities.
Keywords: Symposium; creation of hierarchies; social control; archaism; origins of polis